(untitled) (Global Journal of Science Frontier Research, 2019)
After secretly working on several experiments and observations, Prince Jessii combines all the outcomes and results to present the "theory of everything" which is released this year ahead of the start of a new decade [2020] to open the eyes of everyone to the world of science [physics] and to release an urgent information. This theory tells the world what made them exist, how they existed, how they can still exist. It isn’t fair if humans die every day with all the unfortunate events happening and still to come, when science [physics] is there to save them and prevent all unfortunate events from happening.